Health‐related quality of life as an independent predictor of long‐term disability for patients with relapsing–remitting multiple sclerosis. Issue 6 (24th January 2013) - Baumstarck, K.; Pelletier, J.; Butzkueven, H.; Fernández, O.; Flachenecker, P.; Idiman, E.; Stecchi, S.; Boucekine, M.; Auquier, P.; ,
<x xml:space="preserve">Abstract</x> Background and purpose Predictive factors of long‐term disability in patients with relapsing–remitting multiple sclerosis (RR‐MS) are well known, but the weight of these factors does not explain the entire change of disability. Few studies have examined the predictive value of quality of life (QoL). Objectives To determine the value of the initial level of QoL to predict changes in the disability status of patients with MS and to determine if specific‐MS questionnaires predict more accuracy in these changes than generic questionnaires. Methods Design: multicenter, multi‐regional, and longitudinal study. Main inclusion criteria: patients with RR‐MS subtype and an Expanded Disability Status Scale (EDSS) score lower than 7.0. Sociodemographic and clinical data were recorded at baseline. Every 6 months up to month 24, QoL (MusiQoL and SF‐36) was recorded. At 24 months, individuals were defined into two 'disability change' groups: the worsened and not worsened patients. Results Five‐hundred and twenty‐six patients were enrolled: 386 (83.7%) not worsened and 75 (16.3%) worsened patients at 24 months. The activity of daily living and the relationship with healthcare workers dimensions of MusiQoL questionnaire were independent predictors of change in the EDSS score after 24 months. The physical‐functioning dimension of the SF‐36 questionnaire predicted independently disability change after 24 months. Conclusions Patient‐reported baseline QoL levels provide additional prognostic information on MS disability beyond traditional clinical or sociodemographic factors. These findings reinforce the importance of incorporating a patient's evaluation of their own QoL level during patient monitoring and the assessment of treatment effects.